Analisis Rugi Daya pada Saluran Transmisi Antara Gardu Induk Aur Duri Ke Jurusan Payo Selincah - Marseila, Marseila; Dewi, Rozlinda; Suprapto, Eko (Journal of Electrical Power Control and Automation (JEPCA), 2024)
During the distribution of electric power, there are power losses which occur in both the line and the transformer. Power loss can be identified if the voltage at the transmitting base (generator) and the receiving base is different from research data. Power loss is energy loss that cannot be avoided. It is important to anticipate and examine energy loss in order to ensure it stays within acceptable boundaries. A lack of electricity supply in an area will result in low voltage, even power outages. The voltage and current at peak load every day are taken at 14.00 WIB and 22.00 WIB. The distance from the Aur Duri substation to the Payo route is 19 km, as this transmission line enters the short transmission line. The power losses that occur when sending power from G.I Aurduri to the Payo Selincah department are quite large. However, these losses still meet the requirements for the feasibility of transmission lines according to PUIL PT. PLN (Persero) 2010, namely not more than 10%. The cause of power loss is due to several factors, namely insulator leaks, long distances, environmental temperature, lack of current flowing and the conductor table material used.